The economics of tax policy - Auerbach, Alan J.; Smetters, Kent A. (Kent Andrew) (New York, NY Oxford University Press, 2017)
The debates about the what, who, and how of tax policy are at the core of politics, policy, and economics. 'The Economics of Tax Policy' provides an accessible overview of recent research in the economics of taxation.
Previously issued in print: 2017.
Electronic reproduction.
Keywords: Taxation; Fiscal policy; Finance, Public